2003
DOI: 10.1097/00019606-200309000-00007
|View full text |Cite
|
Sign up to set email alerts
|

PTEN Protein Expression Correlates With PTEN Gene Molecular Changes but not With VEGF Expression in Astrocytomas

Abstract: PTEN gene (10q23) is a relevant tumor suppressor gene whose protein is a phosphatase involved in the control of angiogenesis of some tumors including astrocytomas. There are no studies correlating molecular changes of PTEN and the immunohistochemical expression of its protein (pPTEN) with the expression of vascular endothelial growth factor (VEGF) in astrocytomas. Fifty-six surgically resected brain gliomas, 10 grade 2, 16 grade 3, and 30 grade 4, were studied by a combined approach, consisting of (1) PCR anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…Positivity for mutant IDH1 was recorded when there was strong cytoplasmic staining [19] , for p53 and ATRX when more than 10% of the tumor revealed nuclear staining [18,20] . PTEN positivity was based on the cytoplasmic staining intensity and pattern [21] , and EGFR positivity was based on the grade of membrane and/or cytoplasm staining [22] . The MIB-1 labeling index evaluation was based on nuclear staining of the tumor cell [23] .…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%
“…Positivity for mutant IDH1 was recorded when there was strong cytoplasmic staining [19] , for p53 and ATRX when more than 10% of the tumor revealed nuclear staining [18,20] . PTEN positivity was based on the cytoplasmic staining intensity and pattern [21] , and EGFR positivity was based on the grade of membrane and/or cytoplasm staining [22] . The MIB-1 labeling index evaluation was based on nuclear staining of the tumor cell [23] .…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%
“…It plays an important role in a wide spectrum of physiological activities, such as cell differentiation, senescence, apoptosis, adhesion and migration, and it has recently captured attention from oncobiologists because of its tumor-suppressing properties [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [20] also reported that the expressions of PTEN and VEGF were negatively correlated in hepatocarcinoma (HCC). But there were also notions that no correlation exists between the expression of PTEN and that of VEGF or the tumor angiogenesis [21,22] . The discrepancy may be derived from the fact that different tumor cells are used and the biological characteristics of the different tumor phenotypes differ greatly, which needs further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…69 Alternatively, PCR-based methods to identify LOH and IHC to identify loss of protein expression can be applied with significant correlations. 79 PTEN IHC is often difficult to interpret, however, and discordance with molecular assays is not uncommon, arguing against its routine use. 79,80 TP53 MUTATIONS TP53, a transcription factor and tumor suppressor gene located on chromosome 17p13, is mutated in approximately 50% of all human malignancies, leading to constitutive expression of the p53 protein.…”
Section: Phosphatase and Tensin Homolog Deletionsmentioning
confidence: 99%
“…79 PTEN IHC is often difficult to interpret, however, and discordance with molecular assays is not uncommon, arguing against its routine use. 79,80 TP53 MUTATIONS TP53, a transcription factor and tumor suppressor gene located on chromosome 17p13, is mutated in approximately 50% of all human malignancies, leading to constitutive expression of the p53 protein. 81 Recent studies from The Cancer Genome Atlas network showed alterations involving the p53 pathway in 78% of glioblastomas.…”
Section: Phosphatase and Tensin Homolog Deletionsmentioning
confidence: 99%